Metode RF Filter untuk Perbaikan Kinerja Received Total Wideband Power pada Sistem UMTS - antara, adi surya; Gunantara, N.; Wirastuti, NMAED (Majalah Ilmiah Teknologi Elektro; Vol 15 No 1 (2016): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2016.v15i01p11, 2016)
Cellular communication system with multiple network operators operate on a co-located area (heterogeneus network) causing effect of radio frequency interference. RTWP (received total wideband power) value emerges as indicator radio frequency interference on UMTS system, which is primary contribution of degraded QoS cellular communication system. RF filter butterworth circuit two half section resulted as optimal design to reach the goal compare to the other circuit section . By implemented RF filter has showed improvement indicator perform RTWP on UMTS network operator.   DOI:  10.24843/MITE.1501.11